1979
DOI: 10.1159/000232324
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Characterization of Two <i>Cladosporium herbarum </i>Allergens

Abstract: Two important Cladosporium herbarum allergens (Ag-54 and Ag-32) were partly purified by means of diafiltration, gel filtration and isoelectric focusing. Modifications of quantitative immunological techniques, including autoradiography, were used as assay systems for allergenic activity and to provide a basis for evaluation of the immunological purity of the allergens. Ag-54 appeared to have a molecular weight of approximately 25,000 daltons and an isoelectric point of 5.0. The molecular weight of Ag-32 appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…Certain high-molecular weight carbohydrates are also allergens (46). Only a few fungal allergens have been precisely characterized (47)(48)(49). Allergy to mold and other fungi mediated through immunoglobulin E (IgE) can be proved by skill prick tests or by detection of antigen-specific IgE antiScand J Work Environ Health 1996, vol22, no 1 bodies in a serum sample with any of the available test kits (RAST, Phadiatop, CLA-Mast, etc) (50,51).…”
Section: Allergic Diseasesmentioning
confidence: 99%
“…Certain high-molecular weight carbohydrates are also allergens (46). Only a few fungal allergens have been precisely characterized (47)(48)(49). Allergy to mold and other fungi mediated through immunoglobulin E (IgE) can be proved by skill prick tests or by detection of antigen-specific IgE antiScand J Work Environ Health 1996, vol22, no 1 bodies in a serum sample with any of the available test kits (RAST, Phadiatop, CLA-Mast, etc) (50,51).…”
Section: Allergic Diseasesmentioning
confidence: 99%
“…Clmiosporiiirn is reported to be the most common airborne fungus in temperate zones (Solomon 1978) and in many countries the species C. herbarirni is a major fungal cause of inhalent allergy and allergic asthma in man (Nielsson & Aas 1976, Tarlo et al 1988. Aukrust and Borch (1979) identified two major allergenic components of this organism by extensive CRIE studies, but significant biochemical and immunological differences have been reported among different strains (Sward-Nordmo et al 1984). In the present investigation, six isolates of C. herboriitn were studied with the aim of identifying suitable isolate for a reference standard of this organism.…”
mentioning
confidence: 99%
“…Aukrust and Borch (1979) identified two major allergenic components of this organism by extensive CRIE studies, but significant biochemical and immunological differences have been reported among different strains (Sward-Nordmo et al 1984). In the present investigation, six isolates of C. herboriitn were studied with the aim of identifying suitable isolate for a reference standard of this organism.…”
mentioning
confidence: 99%
“…It is relevant to mention that most of the commercial allergen extracts available for diagnostic and treatment purposes include C. herbarum and C. cladosporoides. 15,16 Makkah is considered to be a twin city situated only 60 km from Jeddah. Population mixture is a daily routine and, in fact, more people travel from Jeddah to Makkah for pilgrimage, prayers and to spend weekends and vacations.…”
Section: Discussionmentioning
confidence: 99%